Evaluating the Role of ACE I/D Polymorphism in Hypertension among Balinese Patients - Dewa Ayu Sri Handani; Ni Nyoman Yudianti Mendra; I Wayan Surya Rahadi; I Dewa Agung Ayu Diva Candraningrat (Poltekkes Kemenkes Surabaya, 2026)
Hypertension continues to pose a major public health challenge worldwide, playing a critical role in the development of cardiovascular diseases and related fatalities. Its pathogenesis is multifactorial, involving both environmental influences and genetic predispositions. Among the genetic factors, the insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene has garnered widespread attention, with previous studies reporting inconsistent associations with hypertension across different ethnicities. This cross-sectional study investigated the relationship between ACE I/D polymorphism and blood pressure in 87 untreated hypertensive patients of Balinese ancestry. Genotyping revealed the II genotype as the most prevalent (63.2%), followed by ID (29.9%) and DD (6.9%). While no significant association was found between genotypes and hypertension staging (p=0.090) or systolic blood pressure (p=0.552). A statistically significant variation was observed in diastolic blood pressure (DBP), with individuals carrying the DD genotype exhibiting the lowest mean DBP (p = 0.022). Similar trends emerged in allele-based analysis, where D allele carriers had significantly lower DBP (p = 0.006). These findings demonstrate an inverse association between the D allele and diastolic blood pressure in this cohort, diverging from traditional risk patterns reported in other populations. This suggests that the ACE I/D polymorphism may act as a potential risk factor modulated by population-specific contexts, highlighting the importance of ethnic diversity in precision medicine for hypertension management.